Legal Protection of the Printing Format of the Newspaper - Al-Zubaidi, Adel Khalil Mahdi (ALBAHITH ALALAMI, 2014)
This research has been devoted to the objective and important issue which is the legal protection of the printing form of the newspaper in the Iraqi press.As this issue constitutes the integrated unit of the printing format in addition to achieving legal protection for the illustrative image used in the press. Such matter, on both level the integrated unit of the printing format and the legal protection, is out of reach of study due to the comprehension of the subject is concerned.Although there is a justification for dealing with both of them together as the explanatory image is one of the foundations on which the printing format of the newspaper is built. This case generates, at least, the same legal subject that appears clearly when addressing the interests or rights of the producer of the printing format of the newspaper and the producer of the illustrative image of the newspaper.Addressing the interests and rights of the producer of a newspaper's printing format requires presenting his legal status in order to determine this subject in dealing with the applicable laws and regulations referring to him, and in particular the Copyright Protection Act No. 3 of 1971.Therefore, in this paper, I will address the legal issues associated with the printing format of the newspaper.